Perancangan Enterprise Resource Planning Modul Benefits Aplikasi SAP dengan Metode SAP Activate Pada PT. XYZ - Putri Miftahul Jannah; Litasari Widyastuti Suwarsono; Putra Fajar Alam (Jurnal Teknik Informatika dan Sistem Informasi, 2018)
PT. XYZ is a private company in construction and heavy equipment rental services. Construction services include housing, apartments, hotels, malls and other properties and renting heavy equipment such as Tower Crane & Passenger Hoist. The number of employees at PT. XYZ increases every year. Ways to maintain employee performance and loyalty is managing appropriate resources by providing compensation and benefits to Employees. Problems in the process of administration benefits at PT. XYZ is taken a long time to make a medical claim. Claim process takes seven days to process until complete. Approximately 30 claims submitted each day in the HRD with the number of claims processed does not match the specified time. The process of administration benefits does not meet the requirements set by the company. PT. XYZ is suitable to implement ERP system with SAP application because of PT. XYZ is already in the enterprise with a large income and a large number of employees. Therefore, the solution of the problem is to design ERP system benefits module at PT. XYZ with SAP software using SAP Activate method. The design can accelerate the process of administration benefits in the company and generate a list of benefit plans for each employee because the ERP system with the SAP application can integrate the HRD division with other divisions in the company.